Child development basics and the importance of play - Jenning, Judy; Blain, Frank; Learning Zonexpress (Owatonna, MN : Learning Zonexpress, 2005)
This program focus on child development, and the child action in growth such as when the baby grap a rattle, when are most kids potty trained, and also how to start a babysitting business, and how to be the best babysitters they can be.
Title from title screen.
Keywords: Child rearing; Child development; Babysitters; Children, Growth